Towards a European helicopter noise calculation method - Tuinstra, M.; Stevens, J.; Oosten, N. van; Olsen, H. (My University, 2018)
Helicopter noise is strongly dependent on flight conditions, exhibiting in addition a pronounced directivity, complicating noise modelling. In land-use planning, the current best practice stems from fixed-wing aircraft and follows a Noise Power Distance approach that is unsuitable to include these features. The European Commission commissioned the development a novel helicopter noise model to be eventually part of a public "European Environmental Model Suite for Aviation". The model embodies a helicopter noise calculation method based on the current state-of-the-art. A clustering strategy has been used to represent the European helicopter fleet, thus avoiding the need for performing noise measurements on all types of helicopters. The method uses an empirical source model, with noise hemispheres to faithfully describe the noise directivity pattern. Emission characteristics of a helicopter type are described by a set of hemispheres measured for a range of conditions within the flight envelope. Atmospheric propagation effects are accounted for to evaluate the noise hindrance experienced on-ground. The latter is based on established public models for atmospheric propagation, ground reflection and surface impedance.